The new populism : democracy stares into the abyss - Revelli, Marco (Verso, 2019)
"The word 'populism' has come to cover all manner of sins. Yet despite the prevalence of its use, it is often difficult to understand what connects its various supposed expressions. From Syriza to Trump and from Podemos to Brexit, the electoral earthquakes of recent years have often been grouped under this term. But what actually defines 'populism'? Is it an ideology, a form of organisation, or a mentality? Marco Revelli seeks to answer this question by getting to grips with the historical dynamics of so-called 'populist' movements. While in the early days of democracy, populism sought to represent classes and social layers who asserted their political role for the first time, in today's post-democratic climate, it instead expresses the grievances of those who had until recently felt that they were included. Having lost their power, the disinherited embrace not a political alternative to -isms like liberalism or socialism, but a populist mood of discontent. The new populism is the 'formless form' that protest and grievance assume in the era of financialisation, in the era where the atomised masses lack voice or organisation. For Revelli, this new populism the child of an age in which the Left has been hollowed out and lost its capacity to offer an alternative"--